THE STORYTELLING TECHNIQUE ASSISTED WITH THE PERSONAL PHOTOGRAPH IN TEACHING SPEAKING SKILL - Jismayadi (Institut Agama Islam Negeri Parepare, 2022)
This research is Classroom Action Research about Improving The Qualiy Of The Teaching And Learning Of Speaking Skill through The Implementation of Storytelling Technique assisted with The Personal Photograph. The main objectives of the research were: (1) to improve the students’ speaking skill in English lesson which was integrated with the other skills, such as listening, reading and writing. (2) to improve the students’ ability in using the language aspects, such as vocabulary, grammar and pronounciation having a direct correspondence to speaking skill. Making used of the classroom action based research procedure, the result of the study conveyed that the implementation of Storytelling assisted with the personal photograph could improve the students’ speaking skill. At the same time it could also improve their ability in using the aspects of the language, such as vocabulary, grammar and pronunciation.